Thermo-economic modelling of micro-cogeneration systems : system design for sustainable power decentralization by multi-physics system modelling and micro-cogeneration systems performance analysis for the UK domestic housing sector - Kalantiz, Nikolaos (University of Bradford, 2015)
Micro-cogeneration is one of the technologies promoted as a response to the global call for the reduction of carbon emissions. Due to its recent application in the residential sector, the implications of its usage have not yet been fully explored, while at the same time, the available simulation tools are not designed for conducting research that focuses on the study of this technology. This thesis develops a virtual prototyping environment, using a dynamic multi-physics simulation tool. The model based procedure in its current form focuses on ICE based micro-CHP systems. In the process of developing the models, new approaches on general system, engine, heat exchanger, and dwelling thermal modelling are being introduced to cater for the special nature of the subject. The developed software is a unique modular simulation tool platform linking a number of independent energy generation systems, and presents a new approach in the study and design of the multi node distributed energy system (DES) with the option of further development into a real-time residential energy management system capable of reducing fuel consumption and CO2 emissions in the domestic sector. In the final chapters, the developed software is used to simulate various internal combustion engine based micro-CHP configurations in order to conclude on the system design characteristics, as well as the conditions, necessary to achieve a high technical, economic and environmental performance in the UK residential sector with the purpose of making micro- CHP a viable alternative to the conventional means of heat & power supply.